Surgical Management of Right Atrial Mass Associated with a Vascular Access Catheter. (11th June 2020) - Ferreira, David; Le, Anthony; Khoo, John; Nguyen, Paul; Jain, Manish; Spicer, Timothy; Juergens, Craig
Abstract : Atrial masses are an uncommon but serious clinical problem. The authors report a case of an atrial mass associated with a tunnelled vascular access catheter in an immunosuppressed haemodialysis patient. In the setting of immunosuppression with fevers, a broad differential for the atrial mass was considered. Multidisciplinary team review was pursued to guide management decisions. Ultimately, surgical excision of the mass was pursued with an excellent result. The causes and management of this complex clinical scenario are discussed.